A educação física nos centros municipais de educação infantil de Maringá: avanços a partir da Lei Municipal N°8392/2009 - Lima, Silvia Bandeira da Silva (2013)
From the understanding of the need to discuss and study the legality and legitimacy of physical education in early childhood education, based on the importance of discipline for the integral development of children, and understand that there is still much to investigate about this theme, we chose if by performing a search in this field of intervention, which aims at analyzing the process of consolidation of Law No. 8392/2009, which determines the inclusion of Physical Education in the curriculum of the Centers for Early Childhood Education in Maringá from 2010. Therefore, it was decided to conduct a survey of the descriptive type, with two specific instruments, a questionnaire composed using open questions, with differentiated structures in accordance with the objectives and individuals to be searched, is composed of 46 directors, 46 educators and 27 physical education teachers working in CMEI's Maringá-PR, the other instrument was an interview with semi-structured, directed to those responsible for the presentation, preparation and implementation of Law No. 8392/2009 and the analysis of Project Political for education in physical education. In organizing the data and tabulating the information collected was used Microsoft Excel ® version 2007 for tabulation, and software (Stastistical Package for Social Sciences) SPSS version 15.0 for statistical treatments. After categorization of the data, the analysis was done using descriptive statistics, proposed by Lüdke and Andrew (1986) and Demartini (1988), in which it sought to analyze elements in accordance with the theoretical. The results showed that the Law n º 8392/2009, was honored only in the year 2012, ensuring discipline as a curricular component required in CMEI's, and that it was essential for the creation of a second Law No. 8992/2011, ensuring the presence of a physical education teacher in all areas of operation of municipal schools. Was accomplished by means of its legality the need for a constant process of continuing education for teacher performance in these spaces. Accordingly, we conclude that the Law n º 8392/2009 allowed the entry of the teachers in these spaces, but the legitimacy of his teaching action is to ensure a formation process that incorporates the needs and expectations of society with respect to propositions legal established.